(untitled) (Singaporean Journal of Business Economics and Management, 2018)
The major challenge for the HR managers today is not recruitment of talented employees but to keep their employees engaged. The top management in every organization is trying to formulate new policies every day to overcome this problem of keeping employees engaged. Therefore, current study entitled "drivers of employee engagement in Indian banking sector" has been undertaken. In order realize the stated objectives the researchers have identified seven key drivers of employee engagement namely Supervision, Quality of working environment, Reliability of information, Communication and quality of information, Pay and benefits, Appraisal process and level of satisfaction and Organizational commitment. The researchers have collected data from 200 respondents working in various banks both public and private sector across Bengaluru city. The validity of the questionnaire was adjudged, using Cronbach’s coefficient (a) was calculated to test the reliability and internal consistency of the responses. We found a significant relationship between the chosen variables with the demographic factors. We found a significant correlation among the chosen variables and with overall satisfaction. Supervision, Pay and benefits, Appraisal process and level of satisfaction and Organizational commitment were the major drivers of employee engagement in banking sector. Based on the analysis a brief summary of findings has been drawn, a meaningful conclusion has been arrived at and the results have been compared with the possible evidence.